Construction of Immune-Related ceRNA Network in Dilated Cardiomyopathy: Based on Sex Differences - Liu, Chang; Liu, Jian; Wu, Daihong; Luo, Shaoling; Li, Weijie; Chen, Lushan; Liu, Zhen; Yu, Bingbo (Frontiers in Genetics, 2022)
Abstract Background: Immune targeted therapyhas become an attractive therapeutic approach for patients with dilated cardiomyopathy (DCM) recently. Genetic predisposition and gender play a critical role in immune-related responses of DCM. This study aimed to perform a bioinformatics analysis of molecular differences between male and female and identify immune-related ceRNA network in DCM. Methods: The gene expression microarray and clinical features dataset of GSE19303 was downloaded from the GEO. Raw data were preprocessed, followed by identification of differentially expressed genes (DEGs) between male and female DCM samples. Crucial functions and pathway enrichment analysis of DEGs were investigated through GO analysis and KEGG pathway analysis, respectively. A lncRNA-miRNA-mRNA network was constructed and a central module was extracted from the ceRNA network. Results: Compared with the female group, male benefit more from IA/IgG immunotherapy. Male patients of DCM had a significant positive correlation with the abundance of inflammatory cells (B cells, memory B cells, CD8+ Tem cells and NK cells). Sex difference DEGs had a widespread impact on the signaling transduction, transcriptional regulation and metabolism in DCM. Subsequently, we constructed an immune-related ceRNA network based on sex differences in DCM, including 5 lncRNAs, 6 miRNAs, and 29 mRNAs. Furthermore, we extracted a central module from the ceRNA network, including 2 lncRNAs (XIST and LINC00632),3 miRNAs (miR-1-3p, miR-17-5p, miR-22-3p) and 6 mRNAs (CBL, CXCL12, ESR1, IGF1R, IL6ST and STC1). Among these DEGs, CBL, CXCL12 and IL6ST expression were considered to be associated with inflammatory cells infiltration in DCM. Conclusions: The identified ceRNA network and their enriched pathways may provide genetic insights into the phenotypic diversity of female and male patients with DCM, and may provide a basis for development of sex-related individualization of immunotherapy.